The Eﬀect of the Reﬂective Interior Elements on the Illuminance Level in Classrooms - Pinthoko Nugroho (Universitas Atma Jaya Yogyakarta, 2022)
Lighting is one of the essential aspects of architectural design because it is crucial for room ambiance. Artificial and natural lighting affect the architectural element and the furniture. Using simulation tools is beneficial for measuring the reflective level of furniture elements to the room's lighting. DIALux Evo3 is computer software to support artificial and natural lighting simulation for interior spaces up to a particular room standard. This study uses the DIALux Evo3 software to conduct the trial-anderror process. The level of reflection on an interior element affects the lux value. This study will focus on the aspects of the ceiling, chairs, and table furniture using the trial and error method by simulating until a difference looms. The focus simulation focuses on setting the reflective coating in the DIALux Evo3 software on ceiling elements, chairs, and tables. The literature method examines aspects of DIALux Evo3 and the points measured in the simulation process. This simulation uses 15 lamps. This study aims to prove that the choice of paint finishing affects the results produced by the vertical illuminance (adaptive) parameter and utilizes technology in architecture. The conclusion is that interior elements such as ceilings, chairs, and tables with reflective elements affect the artificial light. The aspect with low reflectivity requires a high lux value compared to architectural and interior components with high reflectance